Chapter L'agro-ecologia come supporto fondativo dell'eco-territorialismo - Bocchi, Stefano (Territori, 2023)
Agroecology stems from the intelligence of territories; it is a contextualised process of active and participatory cultural, scientific, technological and social elaboration. It can provide a founding humus for eco-territorialism in very tangible terms: identifying alternatives to the current agri-food system, triggering strong change dynamics for ecosystem care, consolidating sustainable practices at different scales, from the cultivated field to the organic district - actions necessary to address the current climate, socio-economic, ecological, global health emergencies; as well as affirming ethical principles of individual and social responsibility, concerning the ways of relating to, respecting and caring for both the weak segments of human population, and the natural resources water, land, air, biodiversity. Agroecological approach, strongly systemic, can therefore contribute to the elaboration of sustainability policies aimed at regenerating of territories and landscapes.